1989
DOI: 10.1177/088307388900400206
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Complications of Hemolytic-Uremic Syndrome

Abstract: Of 78 children identified with hemolytic-uremic syndrome at the Children's Hospital, Boston, from 1976 to 1986, 16 patients (20.5%) had neurological manifestations during their hospitalization. The most common manifestations were significant alterations in consciousness (coma, stupor) in 12 patients, and either generalized or partial seizures in ten patients. Others included hemiplegia (4 patients), decerebrate posturing (3), cortical blindness (2), hallucinations (1), and dystonic posturing (1). Cranial compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 6 publications
7
34
1
Order By: Relevance
“…This prevalence is significantly lower than those estimated in the seven series reported in the literature, but one should keep in mind that (1) the figures given by the French national survey are reliable, (2) our series is supposed to be complete because every pediatric nephrology unit has been directly and individually contacted for this series, and (3) isolated seizures were excluded from our series. The prognosis of neurologic involvement in our series was intermediate among the three most important series (6,8,11) and those of Hahn et al (10). The age of patients who died or continued to have severe disabilities was not significantly lower compared with patients who fully recovered in our series as well in all series of the literature.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…This prevalence is significantly lower than those estimated in the seven series reported in the literature, but one should keep in mind that (1) the figures given by the French national survey are reliable, (2) our series is supposed to be complete because every pediatric nephrology unit has been directly and individually contacted for this series, and (3) isolated seizures were excluded from our series. The prognosis of neurologic involvement in our series was intermediate among the three most important series (6,8,11) and those of Hahn et al (10). The age of patients who died or continued to have severe disabilities was not significantly lower compared with patients who fully recovered in our series as well in all series of the literature.…”
Section: Discussionsupporting
confidence: 47%
“…A search for DϩHUS with neurologic involvement in the literature resulted in retrieval of seven series that totaled approximately 150 patients (5)(6)(7)(8)(9)(10)(11). The French national survey of DϩHUS numbered 1308 cases between 1993 and 2007, and our patients, who were recruited from the same centers that participate to the French survey, include 39 cases in the same period, suggesting that the frequency of neurologic involvement is approximately 3%.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical course of patients with these lesions was favorable, and MRI lesions became smaller on follow-up controls. Brain MRI sequenced controls of patients 6 and 21 reinforce the hypothesis of vasculitic lesion as the main cause of tissue damage, although direct neuronal toxicity could not be disclosed (Hahn et al, 1989). In contrast with previous reports (Theobald et al, 2001), basal ganglia necrosis has not proved to be a bad prognosis factor in our series: our patients did not present extrapyramidal signs, as other authors have reported (Di Mario et al, 1987;Barnett et al, 1995).…”
Section: Commentscontrasting
confidence: 55%
“…VT receptors are present in various troncoencephalic nuclei, the amygdala and the hippocampus, and in the posterior root neurons of the ganglia. This suggests VT may induce primary neuronal damage as well as a vasculitic lesion (Hahn et al, 1989;Hamano et al, 1993;Rivero et al, 2004). This probably happens also at the basal ganglia, especially at putamen nucleae, the most frequent localization of CNS lesions (Nakamura et al, 2003).…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation